Incidência e Caracterização de Lesões Desportivas no Taekwondo segundo o Gênero - Oliveira, Marcelo Rocha de; Bang, Flávio Sung Joo; Quitério, Robison José [UNESP]; Padovani, Carlos Roberto; Oliveira Júnior, Silvio Assis de (My University, 2010)
Taekwondo practice has been associated with physical and biomechanical overloads, which are related to occurrence of sports injuries (SI). However, etiological and nosographic information about SI are limited and conflicting. This study analyzed and characterized the SI in Taekwondo athletes, according to gender. Casuistic integrated 22 athletes, 12 men and 10 women, athletes from São Paulo State Team of Taekwondo, adult category, with 23,6±6,8 years, body weight of 66,0±13,1 kg and 1,72±0,09 m of height. Reported morbidity survey was used to obtain retroactive information to 2009 season. Nosographic variables were analyzed using Goodman’s Test for contrasts among multinomial populations. All athletes reported injuries in the season; 56 cases were registered, determining an injury rate of 2.54 SI/athlete; 26 events (46.4%) occurred in males (2.17 SI/athlete), and 30 (53.6%) were related to women (3.00 SI/athlete). There were predominance of injuries in joints (35,7%) and muscles (39,3%); both genders presented injuries in lower members (82.1%, p<0.01), predominant in combat situations (80.4%, p<0.05), during the preparatory period of training (73.2%). There was a higher treatment request among male athletes (73.1%), which showed high asymptomatic return (69.2%); the female group referred similar proportions of absence and presence of treatment request, collaborating for the greater symptomatic return of these athletes (70.0%). In conclusion, the results support predominance of muscles and joints injuries in lower segments, derived from fighting, involving female athletes.

A prática de Taekwondo envolve solicitações físicas e biomecânicas variadas, predispondo os atletas à ocorrência de lesões desportivas (LD). Informações científicas sobre etiologia e nosografia desses agravos são escassas e inconsistentes. Este trabalho analisou a incidência e caracterizou as LD em desportistas da elite brasileira de Taekwondo. A casuística foi composta por 22 atletas integrantes da Seleção Paulista de Taekwondo, categoria adulto, sendo 12 homens e 10 mulheres, com idade de 23,6±6,8 anos, massa corporal de 66,0±13,1 kg e estatura de 1,72±0,09 m. Como instrumento para coleta de informações, um inquérito de morbidade referida foi adaptado à modalidade e utilizado para o registro de dados retroativos à temporada 2009. As variáveis nosográficas foram analisadas com emprego do Teste de Goodman para contrastes entre populações multinomiais, sendo significante o valor p<0,05. Todos os atletas relataram lesões na temporada alvo do estudo. Foram registrados 56 casos de LD, conferindo taxa de incidência de 2,54 LD/atleta. Destas, 26 (46,4%) foram referidas por homens (2,17 LD/atleta), e 30 (56,3%) por mulheres (3,00 LD/ atleta). Em relação à natureza, constatou-se predomínio de lesões musculares (39,3%) e articulares (35,7%) comparadas às afecções tendíneas (17,9%, p>0,05) e ósseas (7,1%, p<0,01). Quanto à localização, a maioria das lesões envolveu membros inferiores (82,1%, p<0,01), predominantes em situações de combate (80,4%, p<0,05) e ocorridas em período de treinamento específico (73,2%, p<0,05). Em conclusão, as evidências suportam predomínio de lesões musculares e articulares em membros inferiores, derivadas de situações de combate, acometendo, sobretudo, atletas do gênero feminino.
Incidence and Characterization of Sports Injuries in the Taekwondo in relation to gender
Keywords: Taekwondo; Lesões desportivas; Morbidade; atleta